Selenium intake help prevent age-related cataract formation: Evidence from NHANES 2001–2008 - Xu, Baiwei; Liu, Zhongwei; Zhao, Jiangyue; Yu, Ziyan (Frontiers in Nutrition, 2023)
Cataract is one of the leading causes of blindness and visual impairment, about 16 million people around the world. Trace elements play an important role in a variaty of the processes in human body. This study aimed to investigate the association between daily dietary intake of trace elements and age-related cataract incidence. Based on data from the National Health and Nutrition Examination Survey 2001-2008, Iron, zinc, copper, and selenium were conducted in this study among subjects aged 50 years and older for African Americans and 55 and older in US adults. Multivariate logistic regression analysis was used in different models to investigate the association of trace elements intake and cataract. After screening, 7525 subjects were ultimately included in this study. A significant negative association was found between selenium intake and cataract incidence in adjusted models using multivariate logistic regression analysis (model 1: OR =0.998, 95% CI =0.997~1.000; model 2: OR= 0.997 , 95% CI = 0.995~1.000; model 3: OR= 0.998 , 95% CI = 0.995~1.000). After dividing selenium intake into quintiles, significant negative associations between selenium intake and cataract were observed in the first quintile of model 3, the fourth and fifth quintiles of all models. In subgroup analyses adjusted for age and sex, a significant negative association was observed only in women aged 65-74 years. Taking the above results together, our study points out that maintaining daily dietary selenium intake at higher levels is helpful for cataract prevention, and that in creasing daily dietary selenium intake in American women aged 65 to 74 years may contribute to the prevention of age-related cataract. The intakes of iron, zinc, copper may not be associated with age-related cataract.